Viscosity investigation of natural gas hydrate slurries with anti-agglomerants additives. (1st December 2016) - Shi, Bo-Hui; Chai, Shuai; Wang, Lin-Yan; Lv, Xiaofang; Liu, Hui-Shu; Wu, Hai-Hao; Wang, Wei; Yu, Da; Gong, Jing
Highlights: Viscosity of natural gas hydrates slurry is investigated with anti-agglomerants. Hydrates slurry viscosity model is developed based on Einstein effective medium theory. Empirical correlations for non-Newtonian coefficient is extracted from experimental data. Aggregation and broken of hydrates particles was considered by four dimensionless parameters. Abstract: The viscosity of natural gas hydrates slurry in high-pressure hydrates slurry rheological measurement system is investigated, which is meaningful for hydrates risk management to solve flow assurance issues in deep-water offshore field. Based on an appropriate stirring speed and time, a relatively uniform and stable hydrates slurry were formed from a water-in-oil emulsion to study the hydrates formation and slurry viscosity under different water cuts, bath temperatures and AAs concentrations. The influence of water cut on hydrates formation and hydrates slurry viscosity is much more significant than that of bath temperature and AAs concentration. Results indicate that the hydrates volume fraction, the continuous liquid phase viscosity and the dispersion degree of hydrates particles in the slurry are the critical factors to affect the viscosity of natural gas hydrates slurry. Considering both of aggregation and breakage of hydrates particles, a natural gas hydrates slurry viscosity semi-empirical model is developed based on the Einstein effective medium theory. The key parameter non-Newtonian coefficient K of this model is determined by several empirical correlations according to the experimental conditions and fluid properties. The consistence of predicted and experimental data demonstrates the feasibility of this model.